Konflik antara Nahdlatul Ulama, Muhammadiyah, dan Front Pembela Islam - Fadillah, Arroza; Khanif, Dzulkhamd (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2024)
This research aims to examine the role of the people of Kemranjen Village, Banyumas Regency, in the conflict between the Nahdlatul Ulama, Muhammadiyah and the Islamic Defenders Front. Using a qualitative approach and data obtained through interviews. This conflict has a deep meaning for the people of Kemranjen Village in their socio-religious life. This research uses a descriptive method by examining the phenomena experienced by the people of Kemranjen Village. By establishing tolerance, the community is able to strengthen harmony between residents and can develop religious values ​​and foster solidarity among different communities and the community plays an important role in forming religious identity in Kemranjen Village.